FACTORS AFFECTING FINANCIAL DISTRESS WITH ENTERPRISE RISK MANAGEMENT AS A MODERATION VARIABLE - Sitanggang, Tiofanni; Kamaliah, Kamaliah; Ratnawati, Vince (Riau International Conference on Economics, Business and Accounting, 2024)
The aim of this research is to empirically test the influence of the Independent Board of Commissioners, Sales Growth and Leverage on Financial Distress with Enterprise Risk Management as a moderating variable. The research population is all Wholesale and Retail Trade Subsector Companies listed on the Indonesia Stock Exchange for the 2017-2021 period, while the research sample in this study is 50 Wholesale and Retail Trade Subsector Companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The data used is secondary data collected by looking at the Annual Report of the Sample Company published via the website www.idx.co.id. This research uses a data analysis method using tools, namely SPSS Ver. 25. The research results show that the Independent Board of Commissioners, Sales Growth and Leverage have an influence on Financial Distress. Enterprise Risk Management can only moderate the relationship between Sales Growth and Financial Distress, while Enterprise Risk Management was unable to moderate the relationship between the Independent Board of Commissioners and Leverage on Financial Distress. Keyword : Financial Distress, Independent Board of Commissioners, Sales Growth, Leverage, Enterprise Risk Management